EVALUASI IMPLEMENTASI PROGRAM DESA TANGGUH BENCANA (DESTANA) UNTUK MENINGKATKAN KESIAPSIAGAAN MASYARAKAT DI KABUPATEN LAMANDAU - Sarini, Ova; Aquarini, Aquarini; Fatchurahman, M. (Jurnal Progress Administrasi Publik, 2025)
This study evaluates the effectiveness of the implementation of the Disaster-Resilient Village Program (DESTANA) in Lamandau Regency. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation from eight villages selected as research sites. The findings indicate that budget constraints, limited community training, and a lack of coordination among stakeholders are the primary challenges. Only half of the villages have conducted emergency response simulations, with low community participation. This study highlights the importance of equitable budget distribution, community engagement, and enhanced cross-sectoral coordination. The contribution of this research lies in strengthening community-based disaster risk reduction theory and providing strategic recommendations for more inclusive policies. It opens opportunities for further exploration of the social and cultural factors influencing community preparedness in facing disasters.    Keywords: Disaster-Resilient; Policy Implementation; Preparedness